Search for a low-mass τ−τ+ resonance in association with a bottom quark in proton-proton collisions at $$ \sqrt{s} $$ = 13 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Dragicevic, M.; Eroe, J.; Escalante Del Valle, A.; Flechl, M.; Fruehwirth, R.; et al. (Springer Science and Business Media LLC, 2019)
Abstract A general search is presented for a low-mass τ − τ + resonance produced in association with a bottom quark. The search is based on proton-proton collision data at a center-of-mass energy of 13 TeV collected by the CMS experiment at the LHC, corresponding to an integrated luminosity of 35.9 fb−1. The data are consistent with the standard model expectation. Upper limits at 95% confidence level on the cross section times branching fraction are determined for two signal models: a light pseudoscalar Higgs boson decaying to a pair of τ leptons produced in association with bottom quarks, and a low-mass boson X decaying to a τ-lepton pair that is produced in the decay of a bottom-like quark B such that B → bX. Masses between 25 and 70 GeV are probed for the light pseudoscalar boson with upper limits ranging from 250 to 44 pb. Upper limits from 20 to 0.3 pb are set on B masses between 170 and 450 GeV for X boson masses between 20 and 70 GeV.
Keywords: boson: mass; Compact Muon Solenoid; lepton; GeV-cms; Higgs bosons; optical detector readout concepts; bottom: particle identification; QC770-798; Physics, Particles & Fields; high energy physics; high energy physics; experimental particle physics; LHC; CMS; physics; beyond two generations; excited top quark; hadron-hadron scattering (experiments); supersymmetry; beyond standard model; lepton production; data acquisition concepts; detector control systems (detector and experiment monitoring and slow-control systems, architecture, hardware, algorithms, databases); modular electronics; optical detector readout concepts; particle physics experiments; data; Higgs; muon; High Energy Physics - Experiment; Tau physics; Hadron-Hadron scattering (experiments); [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; hardware; Extra dimensions; info:eu-repo/classification/ddc/530; Physical Sciences; tau: pair production; CMS; Physics; Hadron-Hadron scattering (experiments), Higgs physics, Tau Physics; ddc:530; hadron-hadron scattering (experiments); Higgs physics; Nuclear & Particles Physics; mass dependence; channel cross section: branching ratio: upper limit; Hadron-Hadron Scattering (Experiments); CERN LHC Coll; data; Physical Sciences; modular electronics; Physique des particules élémentaires; Centre for High Energy Physics; detector control systems (detector and experiment monitoring and slow-control systems; Particle physics; Hadron-Hadron scattering (experiments); Higgs physics; Tau physics; LHC; databases); jet: bottom; physics; beyond standard model; Higgs particle: pseudoscalar particle; resonance: leptonic decay; p p: scattering; Higgs Physics; architecture; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; Tau Physic; Particles & Fields; hadron-hadron scattering (experiments); higgs physics; tau physics; jet: associated production; Hadron-Hadron scattering (experiments); Higgs physics; Tau Physics; Extra dimensions; Pp collisions; Higgs bosons; Tau leptons; PAIR; Events; algorithms; lepton production; Events; PAIR; beyond two generations; muon; Hadron-Hadron scattering (experiments); Higgs physics; Tau Physics; Nuclear and particle physics. Atomic energy. Radioactivity; S055h2d; S055h2o; ЭБ БГУ::ЕСТЕСТВЕННЫЕ И ТОЧНЫЕ НАУКИ::Физика; Tau leptons; data acquisition concepts